COOPERATIVE LEARNING TECHNIQUES TO IMPROVE STUDENTSâ TRANSLATION - Yuliasri, Issy (Faculty of Languages Ã¢â¬â¹Ã¢â¬â¹and Arts, State University of Semarang, 2014)
This classroom action reserach aimed at applying the Cooperative Learning techniques, particularly the Jigsaw and Think-Pair-Share techniques, to help students improve their Indonesian-English translation skill, especially in terms of diction, grammar, and rendering of message/content of the text. The research was done in one âTranslation 2â class of the English Literature Program, the English Department of UNNES. This research showed positive results, revealing that the application of Cooperative Learning techniques could improve studentsâ skill in translating, particularly in terms of diction, grammar, and rendering of message/content of the text. This was seen from the results of evaluation of the process and products during the research period. With the application of Cooperative Learning techniques, the evaluation of translation products showed significant improvement in studentsâ translation, particularly in terms of diction, grammar, and rendering of message/content of the text. The results of observation and questionnaire also showed that in general students were more active, motivated, enthusiatic, interested, and they gained better understanding of translation techniques. The students admitted that with Cooperative Learning techniques they could learn easily as they got inputs from their teammates, and they became aware of their mistakes. In addition, with group works they could get varied translations.